2015
DOI: 10.1016/j.jnucmat.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Laser cleaning of diagnostic mirrors from tokamak-like carbon contaminants

Abstract: This paper presents a laboratory-scale experimental investigation of laser cleaning of diagnostic First Mirrors (FMs). Redeposition of contaminants sputtered from tokamak first wall onto FMs surface could dramatically decrease their reflectivity in an unacceptable way for the functioning of the plasma diagnostic systems. Laser cleaning is a promising solution to tackle this issue. In this work, pulsed laser deposition was exploited to produce rhodium films functional as FMs and to deposit onto them carbon cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…For this reason we decided to use UV laser light for all the cleaning experiments here reported. Such a sharp variation of the cleaning efficacy depending on the laser wavelength was not observed in the case of carbon contamination [16]. It can be explained considering that W-based contaminants are (to different extents) oxidized, and thus they present an optical band gap which inhibits the absorption of NIR photons (the band gap for crystalline WO 3 is about 2.8 eV, while the photon energy for λ = 1064 nm is 1.17 eV).…”
Section: Laser Cleaning Procedures and Process Parametersmentioning
confidence: 94%
See 4 more Smart Citations
“…For this reason we decided to use UV laser light for all the cleaning experiments here reported. Such a sharp variation of the cleaning efficacy depending on the laser wavelength was not observed in the case of carbon contamination [16]. It can be explained considering that W-based contaminants are (to different extents) oxidized, and thus they present an optical band gap which inhibits the absorption of NIR photons (the band gap for crystalline WO 3 is about 2.8 eV, while the photon energy for λ = 1064 nm is 1.17 eV).…”
Section: Laser Cleaning Procedures and Process Parametersmentioning
confidence: 94%
“…The laser fluence (defined as the energy per pulse divided by the laser beam size) for each wavelength must be chosen according to the strict requirement of leaving the mirror's surface undamaged during the laser cleaning treatment. In [15] and [16], we found that the damage threshold for bare highly-oriented Rh coatings deposited on Si was higher than 350 mJ cm −2 for NIR and 150 mJ cm −2 for UV pulses, using the irradiation procedure described above. Due to some concerns about the stability of the laser system during UV operation, the laser fluence for the UV cleaning trials described hereafter was set to 110 mJ cm −2 .…”
Section: Laser Cleaning Procedures and Process Parametersmentioning
confidence: 94%
See 3 more Smart Citations